2016
DOI: 10.1002/2016jb013410
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Ultrasound Spectroscopy studies of Berea sandstone at high temperature

Abstract: Resonant Ultrasound Spectroscopy was used to determine the elastic moduli of Berea sandstone from room temperature to 478 K. Sandstone is a common component of oil reservoirs, and the temperature range was chosen to be representative of typical downhole conditions, down to about 8 km. In agreement with previous works, Berea sandstone was found to be relatively soft with a bulk modulus of approximately 6 GPa as compared to 37.5 GPa for α‐quartz at room temperature and pressure. It was found that Berea sandstone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Hence, the mechanical behavior of these kinds of rocks at high temperature has also been studied in order to guide some underground high‐temperature engineering works such as underground coal gasification. Changes in peak strength, peak strain, failure mode, elastic modulus, and P‐wave velocity of sandstone and limestone are found to be consistent with granite after high‐temperature treatment 25‐30 . For example, Zhang et al 30 reported that the peak strength decreased slowly, the elastic modulus decreased at a relatively rapid rate, and the peak strain increased slowly when sandstone was subjected to high‐temperature treatment.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Hence, the mechanical behavior of these kinds of rocks at high temperature has also been studied in order to guide some underground high‐temperature engineering works such as underground coal gasification. Changes in peak strength, peak strain, failure mode, elastic modulus, and P‐wave velocity of sandstone and limestone are found to be consistent with granite after high‐temperature treatment 25‐30 . For example, Zhang et al 30 reported that the peak strength decreased slowly, the elastic modulus decreased at a relatively rapid rate, and the peak strain increased slowly when sandstone was subjected to high‐temperature treatment.…”
Section: Introductionmentioning
confidence: 82%
“…Changes in peak strength, peak strain, failure mode, elastic modulus, and P-wave velocity of sandstone and limestone are found to be consistent with granite after high-temperature treatment. [25][26][27][28][29][30] For example, Zhang et al 30 reported that the peak strength decreased slowly, the elastic modulus decreased at a relatively rapid rate, and the peak strain increased slowly when sandstone was subjected to high-temperature treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The Berea sandstone, a good reservoir rock in view of relatively high porosity and permeability, often finds application as a reference material in the event that the constituents of a reservoir are not known. For further details about the characteristics of Berea sandstone, the reader can refer to the book by Jaeger et al [52], as well as to the papers by Shankland et al [36], Davis et al [41], Khaled et al [53], Coyner [54], Davis [55], and Ikeda et al [56].…”
Section: Numerical Simulationmentioning
confidence: 99%
“…More generally, the pore pressure diffusion seems to be a triggering mechanism for earthquake swarms [33]. There is a huge interest toward the research in wave propagation in porous media, starting with Biot's early works [5,34,35], continuing with the studies by Wilson and Aifantis [12], Beskos et al [14], Beskos and Papadakis [15], Shankland et al [36], Berryman and Wang [37], and with more recent studies by Olny and Boutin [18], Mu¨ller et al [31], Svanadze [38], Ciarletta et al [39], Straughan [40], Davis et al [41], Gales x and Chirit xa˘ [42], Chirit xaȃ nd Arusoaie [43], and Chirit xa˘and Gales x [44]. Based on the results by Nield [45], Franchi et al [46], and Svanadze [47], Chirit xa˘ [48] develops a mathematical model able to describe the evolutive behavior of triple porous media under local thermal non-equilibrium hypothesis: taking into account anisotropic and inhomogeneous materials, the constitutive equations are given, showing the terms connecting pressures and temperatures at the different pore scales.…”
Section: Introductionmentioning
confidence: 99%